Prothrombin Complex Concentrate in Emergency Department - Višnja Nesek Adam; Ingrid Bošan-Kilibarda (Acta Clinica Croatica, 2022)
Coagulation abnormalities are common in bleeding or critically ill patient and hemostatic management remains a major challenge for the emergency physician. Management of bleeding patients consists of bleeding control, restoration of blood volume, and correction of any associated coagulopathy. Traditionally, the fresh frozen plasma (FFP) is used for correction of coagulopathy to manage and prevent bleeding, but today Prothrombin complex concentrates (PCCs) offer an attractive alternative because they offers a number of advantages over FFP, including lower infusion volume, rapid IN R normalization, faster availability, lack of blood group specificity, and better safety profile. The aim of the present review is to provide an short overview about using PCC, their indication, efficacy and safety in different bleeding setting’s.